Pemeriksaan Aldosterone/Renin Ratio sebagai Prediktor Penyakit Ginjal Kronis pada Penderita Hipertensi - Juliani Dewi (MEDICINUS, 2022)
The prevalence of chronic kidney disease (CKD) is increasing. Hypertension is an established risk factor of CKD, yet found prevalent in Indonesia. To date, there is no test that can be used as predictor of , especially hypertensive patients. Recently, the relationship between aldosterone level (plasma aldosterone concentration/PAC) with hypertension and CKD has been extensively studied. Advanced studies have found that aldosterone/renin ratio (ARR) can be a promising parameter to predict the occurrence of CKD. This result brings hope for hypertensive patients, as we are able to predict not only the occurrence of CKD, but also the probability of cardio- and/or cerebrovascular events. Particularly for East Asia ethnic groups that are known to consume a relatively high amount of salt, ARR could also be a marker of salt intake sensitivity that may lead to a proper salt restriction in daily diet.